2005
DOI: 10.1017/s1743921305005958
|View full text |Cite
|
Sign up to set email alerts
|

Observations of globular clusters with FLAMES

Abstract: Abstract. We present preliminary results of a few observing programs conducted with the FLAMES fiber facility at VLT2 ESO telescope. These programs show the large potentiality of FLAMES for investigations of globular clusters. The programs described here concern the derivation of precise reddening and metallicity for globular clusters, and the derivation of abundances for stars on the main sequence of ω Cen. Reddenings with errors of ∆E(B − V ) = 0.005 mag and metallicities with errors of ±0.02 dex (in a scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Combined with the results on SGB stars by Gratton et al (2012c) we can conclude from our study that stars on the faint SGB are predominantly -but non only -N-rich (hence they occupy a redder position on the RGB, in Strömgren colours), while the stars on the bright SGB are about 1/3 N-rich and 2/3 N-poor (hence they are mostly blue in the Strömgren colours).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Combined with the results on SGB stars by Gratton et al (2012c) we can conclude from our study that stars on the faint SGB are predominantly -but non only -N-rich (hence they occupy a redder position on the RGB, in Strömgren colours), while the stars on the bright SGB are about 1/3 N-rich and 2/3 N-poor (hence they are mostly blue in the Strömgren colours).…”
Section: Resultssupporting
confidence: 81%
“…First, Yong & Grundahl (2008) found a correlation of Zr and La with Al in a few bright giants in NGC 1851. Carretta et al (2011a) confirmed this correlation using a large sample of more than 120 giants; Gratton et al (2012b) found a close correlation between Na and Ba among RHB stars; and finally Gratton et al (2012c) found (i) clearly different Sr and Ba abundances between the faint (higher abundances) and bright subgiant branches (SGBs) found by Milone et al (2008); and (ii) that a spread exists within both sequences.…”
Section: Resultsmentioning
confidence: 61%